Institutional navigation of oceans governance: Lessons from Russia and the United States Indigenous multi-level whaling governance in the Arctic - York, Abigail M.; Zdor, Eduard; BurnSilver, Shauna; Degai, Tatiana; Monakhova, Maria; Isakova, Svetlana; Petrov, Andrey N.; Kempf, Morgan (Earth System Governance, 2022)
Oceans governance occurs through overlapping, multi-level institutions that often fail to recognize Indigenous sovereignty and self-determination. The International Whaling Commission (IWC) provides pathways for recognizing Indigenous rights. However, observed power asymmetries and cross-level local to international conflicts threatened subsistence rights and generated research and advocacy fatigue for Chukchi, I˜nupiat, Saint Lawrence Island Yupik, and Siberian Yupik communities in the USA and Russia. We conduct an institutional analysis of Indigenous bowhead whaling governance based upon lived experiences of Indigenous authors, primary documents from co-management organizations, national agencies, the IWC, and extant literature. We explore how Indigenous co-management organizations increased sovereignty and self-determination for communities whose culture, identities, livelihoods, and origins are intimately connected to marine mammal hunting. Our study also provides lessons for the United Nations Decade for Ocean Science on the challenges of institutional navigation and the role of embodied resurgent practice amongst Indigenous communities within Earth system governance. Faculty Reviewed